2013
DOI: 10.1177/016146811311500307
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Online and Blended Learning: A Meta-Analysis of the Empirical Literature

Abstract: Background/Context Earlier research on various forms of distance learning concluded that these technologies do not differ significantly from regular classroom instruction in terms of learning outcomes. Now that web-based learning has emerged as a major trend in both K–12 and higher education, the relative efficacy of online and face-to-face instruction needs to be revisited. The increased capabilities of web-based applications and collaboration technologies and the rise of blended learning models combining web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
529
1
47

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,068 publications
(611 citation statements)
references
References 54 publications
34
529
1
47
Order By: Relevance
“…Moreover, this part of the study is limited to just investigating students' perception, but not focusing on how they perform the subjects learned. Just like the findings from Means et al (2013) which indicated that students perform better achievement during online learning rather than offline learning. This might be a reference for further research that investigating what the students like and dislike is as important as analysing students' learning performance.…”
Section: Data Obtained From Interviewsupporting
confidence: 51%
“…Moreover, this part of the study is limited to just investigating students' perception, but not focusing on how they perform the subjects learned. Just like the findings from Means et al (2013) which indicated that students perform better achievement during online learning rather than offline learning. This might be a reference for further research that investigating what the students like and dislike is as important as analysing students' learning performance.…”
Section: Data Obtained From Interviewsupporting
confidence: 51%
“…In longitudinal research, it has been proven that the use of technology in combining models of curriculum material presentation can significantly improve student learning outcomes. In 23 long-term studies conducted by the US Department of Education, it was found that blended learning improved learning outcomes more than the face-to-face model itself [4]. Thus, it can be concluded that the blended learning presentation system is used for four reasons, namely, (a) adapting to the needs of students, (b) increasing the level of communication more productively, (c) saving on the average cost of providing education per student, and (d) improving learning outcomes.…”
Section: The Effect Of a Blended Learning Model On Students' Learning Process And Outcomementioning
confidence: 99%
“…Studies have garnered mixed results regarding online learning's efficacy. Although some studies show FOL (Means et al, 2013;Mullen, 2019) and hybrid (Korach & Agans, 2011;Means et al, 2013) modes can be as or more effective than F2F learning, other studies have found that some students do not do as well in an online format (e.g., Bettinger et al, 2017;Figlio et al, 2013). There is some indication that the effectiveness of different modalities may differ by race and prior academic performance.…”
Section: Efficacy Of Delivery Modesmentioning
confidence: 99%